AN ANALYSIS OF VERBAL AND NON-VERBAL SIGN IN MAYBELLINE COSMETIC ADVERTISEMENTS - Yeni Ruscita Dewi (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
In this study concern with the verbal and visual signs that in Cosmetic Advertisements. The study aims to find out the kinds of verbal and non-verbal signs also to describe the meaning of verbal and non-verbal signs inMaybelline Cosmetic Advertisements. This study used qualitative methods to collect data and the data were takenfrom he internet and maybelline website. To analyze the data this study used the theory by Saussure (1983) and the theory by Barthes (1967) to identify the meaning of verbal and visual signs inMaybelline Cosmetic Advertisements. The researcher found 27 verbal signs and 19 non-verbal signs. While the denotative meaning, the researcher found 22 and for the connotation found 23. The used of connotative meaning dominant in all advertisements because the advertiser use hidden meaning to convey the message and attract the attention of consumers so they are curious to try to use the product.